PERBANDINGAN PERENCANAAN JEMBATAN KOMPOSIT BERDASARKAN SNI 1725:2016 DAN AASHTO 2020 - Dedi Saputra (LPPM Universitas Abdurrab, 2025)
This research presents a comparison of bridges design with two bridge regulations. SNI 1725:2016 and AASHTO 2020 covering loading, loading combinations, moments, shear forces and deflections. The bridge discussed is a composite bridge with the assumption of a simple beam. The working loaded includes dead load, vehicular live load, temperature load, wind load and earthquake load. The earthquake load is calculated based on SNI 2833:2016 because the location is assumed to be in DKI Jakarta. Based on the results of the research, it can be concluded that moments and shear forces due to loading in SNI 1726:2016 are not too much different from AASHTO 2020. So It can be said that the SNI 1725:2016 regulations are very safe to use for bridge design. In addition, bridge loading for AASHTO 2020 loading include the tandem load that does not exist in SNI 1725:2016.